Metodología para la enseñanza de la estimación de la incertidumbre de medición en experimentos de física - Llamosa R., Luis Enrique; Medina B., Milton Humberto; Cano U., Jennyfer Alejandra (Revista Científica, 2011)
A generic methodology for teaching the estimation of measurement uncertainty of experimental results is presented. This methodology has been designed and implemented in the laboratories of physics that gives the Department of Physics of the Universidad Tecnológica de Pereira, with the aim of creating a culture around this issue. The methodology is based on the GTC-51 standard, "Guide to the expression of uncertainty in measurement" based on international standards that are currently used in science, industry and legal. This standard has been worked out thoroughly by the electrophysiology group in the Department of Physics of the UTP, in its research in metrology, able to implement through projects co-financed by COLCIENCIAS. As a result of this experience has generated a culture that promotes the expression of experimental results with the corresponding estimate of measurement uncertainty, starting from the Laboratory of Physics I to the experimental results obtained in undergraduate work and research developments made by the research groups of our department.